Optimization of Variable Thickness Plates by Genetic Algorithms - M. Pyrz (Engineering Transactions, 2015)
The implementation of genetic algorithms to the optimal design of variable thickness plates is presented. Thin, elastic, piecewise constant thickness plates subjected to bending are investigated. The material distribution that minimizes the structural strain energy under constant volume constraint is searched. In numerical examples, square plates loaded by uniform normal pressure are optimized for different boundary conditions. The best designs are compared with the worst solutions, corresponding to the maximization of the strain energy. Significant changes in strain energy can be achieved by modifying thickness distribution for the same material volume. The performances of the approach are discussed.